Rancangan Teknis Penambangan Batukapur pada WIUP OP 412 Ha di PT Semen Padang - Sugiono Sugiono; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2019)
Mining technical design is a design process that is technically very important to do before the start of mining activities. In Indonesia, the government policy on mining engineering is regulated in the Minister of Energy and Mineral Resources Decree No. 1827K/30/MEM/2018 concerning Good Code of Practice for Mining Engineering. In this study, the author discusses the technical design of limestone mining at PT Semen Padang. The purpose of this technical design of mining is to get an overview of the stages of work in the limestone mining process to achieve the production target. Work starts from the geological modeling process in the form of block models. Furthermore, the work continued to the stage of making the ultimate pit limit design. Production scheduling is only for 2019, with proposed mining of 10,839,515 tons. With the provisions of the mining production target per three months, then the push back design is carried out. Next is the calculation of tool productivity. With known production targets and mining equipment productivity, mine scheduling can be done last.Keywords: Block model, ultimate pit limit, production scheduling, push back, and mine scheduling